Information Retrieval From The World Wide Web - Fauziah, Baharum (1995)
This dissertation is being presented as a partial requirement for the degree of Master of Software System Technology in the University of Sheffield. The thesis on title “Information Retrieval From The World Wide Web” is undertaken from May to September 1995. The aim of this project is to design a system which uses the Web searching technology. When this system is completed, it can be implemented to do indexing and searching any interested document that stored in the Web. This application may give some benefits to its users especially to the Department of Computer Science, University of Sheffield. Ideally, this system is developed by using one of the software engineering approaches called “Incremental delivery strategy”. The project began with the feasibility study of the techniques used in Information Retrieval and also the components involved in the World Wide Web and continued with the process of requirement analysis. The designer chose to use the data flow diagram method in order to show the design of this system. After the design was done, the system was implemented by using the C programming language and aided by the World Wide Web Library (or known as libwww). This dissertation describes the development stages of this system. Problems faced and suggestions to recover were presented as discussions. And other relevant information was attached as appendixes.